Output volatility in the OECD: are the member states becoming less vulnerable to exogenous shocks? - Andraz, Jorge Miguel (2014)
This paper analysis the vulnerability of the OECD member states to external shocks by estimating the degree of asymmetric effects from positive and negative shocks. We use asymmetric conditional heteroscedasticity models with endogenously determined regime changes in a context of progressive moderation in both moments. The results suggest that recessions are associated with higher volatility and significant leverage effects. The estimated impacts of negative and positive shocks amount to 0.961 and 0.028, respectively. The disaggregated analysis over different periods reveals an increasing pattern of these asymmetries, as well as huge differences among the countries. The country-specific analysis suggest an increasing vulnerability to negative exogenous shocks in Australia, Denmark, Finland, Japan, Mexico, the Netherlands, Turkey and the United Kingdom, although with different levels, and decreasing vulnerability in Canada, Greece, Italy and New Zealand. Finally, some economies seem to have developed higher levels of immunity to external shocks by reaching balanced effects from positive and negative shocks. Among these are the largest European economies, together with the northern economies, the United States and the wealthiest economies of Luxembourg and Switzerland.